2013
DOI: 10.1093/bja/aet002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of propofol on mid-latency auditory-evoked potentials in children

Abstract: Propofol affects MLAEP latencies and amplitudes in children in a dose-dependent manner. MLAEP measurement might therefore be a useful tool for monitoring depth of propofol anaesthesia in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…This study has shown that AEP latency exhibited similar changes in different subjects and at different acoustic intensities during anesthesia ( Figs 2e , 3a ), corroborating previous studies 36 37 38 39 40 . However, AEP amplitude changed with greater variability during anesthesia ( Figs 2g , 3d ), consistent with other reports 14 41 .…”
Section: Discussionsupporting
confidence: 91%
“…This study has shown that AEP latency exhibited similar changes in different subjects and at different acoustic intensities during anesthesia ( Figs 2e , 3a ), corroborating previous studies 36 37 38 39 40 . However, AEP amplitude changed with greater variability during anesthesia ( Figs 2g , 3d ), consistent with other reports 14 41 .…”
Section: Discussionsupporting
confidence: 91%
“…In addition, ABRs are used in combination with evoked potentials from other modalities to monitor coma prognosis (Guérit 2005;Fischer et al 2006; see below), or in isolation to corroborate brain death (Machado et al 1991). In the surgical theatre, MLR is used to monitor the depth of anaesthesia in adults (Bell et al 2004) and children (Kuhnle et al 2013). It has been recently shown that, compared with the traditional clinical assessment of depth of anaesthesia, MLR monitoring led to a reduction in a) the amount anaesthetic drug requirement, b) the use of vasopressors to manage hypotension, and c) consequential cognitive impairment (Jildenstål et al 2011).…”
Section: Utility Of Aerp For Clinical Practicementioning
confidence: 99%
“…Six studies described MLAEP during propofol anesthesia 20,21,24,27,29,32 . The effect of propofol on the components of the unprocessed MLAEP in children (with a mean age of 8.6 years) has been described by Kuhnle et al 21 They observed a dose related increase of latencies (Na, Pa, Nb and P1) and decreasing amplitudes.…”
Section: Resultsmentioning
confidence: 97%
“…For these four studies, the risk of bias in the reference standard were rated as unclear. Two studies were rated unclear for their risk of bias in the domain of “Flow and Timing”, because one study was terminated prematurely due to change in the anesthesia practice 18 and the other failed to generate data from 4 of the 14 patients 21 . Seven studies allowed premedication for their patients and were therefore rated as “unclear” for applicability concerns of patient selection 17,18,20–24 .…”
Section: Resultsmentioning
confidence: 99%